GIS-based multi-criteria evaluation to develop elephant suitability habitat model in Peninsular Malaysia - Aini, Suhaida (2017)
The greatest threats to biodiversity are the loss of habitat and forest fragmentation. Both of these factors are also the major threats to the survival of Asian elephants throughout Asia including within the Peninsular Malaysia. In addition, forest fragmentation creates a situation where the protected areas (PAs) are isolated from one another. As a result, the biodiversity resources may be reduced, resulting in the difficulty for some of the species such as the Asian elephant to breed and to look for sources of food and ultimately to move out of the areas. Hence, this study aims to develop an Asian elephant habitat suitability model using geoinformation tools with multi criteria evaluation (MCE) techniques. The satellite imageries and topographical maps were used to generate the environmental and topographical habitat parameters encompassing land cover, forest type, water resources, Digital Elevation Model (DEM), slope and salt-lick respectively. The elephants’ home range was determined using satellite transmitter data in order to obtain the habitat preference parameters and their location distribution pattern. Result shows that the highly suitable areas for elephant habitat are mainly concentrated within the Ulu Jelai Forest Reserve, which is a secondary forest, and outside the protected areas. The developed model suggests that long-term conservation of this species requires more effective management of the large continuous areas (both within and outside PAs) consistent with the implementation of National Elephant Conservation Action Plan (NECAP) through the Managed Elephant Range (MERs) program and the construction of eco-viaduct in Peninsular Malaysia. The general Asian elephant suitability habitat map was classified into four levels of suitability with the total percentage of “highly suitable” consists of 43%, followed by “moderately suitable” at 41%, “lowly suitable” at 10% and 6% is “not suitable”. Moreover, this study is capable of evaluating the parameter habitat criteria applied with the ability to modify or to add in order to provide habitats with good quality within their existing natural habitat. Tolerance to elephants presence outside PAs is a key recommendation that food resources are often abundant for Asian elephant. Therefore as an umbrella species, the in situ management of Asian elephants outside the protected areas is critical for their conservation.